A influência de fenômenos climáticos de macroescala (El Niño e La Niña) no regime das chuvas na bacia hidrográfica Paraguai 3 - Hiera, Mitchel Druz (2016)
Recent discussions in the national and global level, concerning environmental issues, always result in alert regarding the inappropriate use of the natural resources. Thus, it is assumed that the climate is an important factor to be considered in the projects related to human activities, primarily for those who depend on the climatic environment effective way. This research has the general goal to investigate the rainfall in Paraguay Basin 3, portion further north in the Hydrographic Region of Paraguay, seeking a connection with large-scale climatic events El Niño and La Niña. To meet this goal, we analyzed the rainfall heights located stations in the municipalities of Arenápolis, Barra do Bugres, Cáceres, Rondonópolis and Itiquira, in a period between 1972 and 2012. To these precipitation values was applied to standard-year rating to determine the wet years, aimed at rainy, usual, tending to dry and dry, in annual and seasonal scale. For the periods considered anomalous (rainy or dry), tried to relate these anomalies to the interaction of large-scale El Niño and La Niña. Plus the role of ENSO, it was atmospheric dynamics over the anomalous periods through the identification and quantification of the participation of the various air masses that act on the study area. After individual analysis of the five municipalities, an average between them was calculated that came to represent the rainfall regime of Paraguay Basin 3. Among the results is evidence that precipitation is tending to decrease in the final years of the time series analyzed in the study area. Also found that the El Niño and La Niña are not solely responsible for the rainfall variability that is happening in the region, with a view that was not found one rainfall pattern when the interaction of those events.